PENGARUH RASIO MARJIN LABA KOTOR DAN RASIO PERTUMBUHAN PENJUALAN TERHADAP RASIO MARJIN LABA BERSIH DI PT SERASI AUTORAYA CABANG BANJARMASIN - Marliani, Gusti; Suntoro, Suntoro (MEDIA RISET EKONOMI [MR.EKO], 2023)
This article is motivated by the condition of unstable income movements and indicates the situation or condition of the company, decision making and policies in managing operations to increase profitability. This article aims to determine whether the gross profit Marjin ratio and sales growth ratio are factors that affect the net profit ratio at PT. Serasi Autoraya Banjarmasin branch. This article was prepared using a descriptive method and a quantitative approach. The research data is secondary data taken from the financial statements of PT. Serasi Autoraya and equipped with literature and documentation studies, which are processed statistically and quantitatively using SPSS. The results of this study conclude that the gross profit Marjin ratio variable has a partial effect on the net profit Marjin ratio, while the sales growth ratio variable has no partial effect on the net profit ratio. Simultaneously, the ratio of gross profit Marjin and sales growth ratio has no significant effect on the ratio of net profit Marjin at PT. Serasi Autoraya Banjarmasin branch. The implication of this research is that the company must pay attention to other factors to increase the company's net profit, besides that the company must also pay attention to the situation, market conditions and trends, customer portfolio, asset management and operations so that the company's net profit can be maximized.